Application of the AHP and PROMETHEE II individual decision-making methods and the Condorcet group decision-making method in the selection of a multipurpose armored wheeled combat vehicle - Živković, Miša D.; Božanić, Darko I.; Suknović, Milija M.; Delibašić, Boris V. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Wheeled armored combat vehicles are combat systems that are increasingly present in modern armed conflicts, especially in operations against asymmetric threats. The global wheeled armored vehicle market is constantly growing, which reflects their application in a wide range of missions and tasks of armed forces. The existence of numerous models of these vehicles with different technical and exploitation characteristics, along with the possibility of adaptation to specific needs, further complicates the choice of the most suitable alternative. The paper presents the case of solving the problem of selecting the most suitable multi-purpose medium-class wheeled armored vehicle with a 4x4 drive formula when choosing one of the four alternatives, using individual and group multi-criteria decision-making methods. Methods: In the paper, the methods of multi-criteria decision making were applied to solve problems in the field of complex combat systems selection. Experts from the field of tactics with weapon systems have ranked the alternatives following the defined criteria using the AHP (Analytic Hierarchy Process) and the PROMETHEE II (Preference Ranking Organization Method for Enrichment Evaluations II) methods. The results obtained by individual decision making were subjected to the Condorcet method of group decision making to make a final decision. Result: Selection of the most suitable vehicle by the defined criteria. Conclusion: Solving the problem involves taking into account the views of military experts regarding the optimization of multiple criteria to provide the best performance vehicle suitable for use in various missions. The choice of a multi-purpose wheeled armored combat vehicle is a complex process influenced by numerous factors that cannot be analyzed objectively without the application of adequate mathematical models.